A State Feedback DFIG Power Control for Wind Generation - Filho, Alfeu J. Sguarezi; Murari, André L. F.; Capovilla, Carlos Eduardo; Altuna, José A. T.; Jacomini, Rogério V. (Eletrônica de Potência, 2015)
This paper proposes a state feedback controller for doubly-fed induction generators at variable speed wind. The controller uses pole placement technique, stator flux orientation, and state feedback rotor current vector loops. None conventional PI controller is used on the control. Its algorithm calculates the voltage vector to be supplied to the rotor to certificate that the active and reactive power follow their desired reference values. Experimental results obtained in a hardware setup are carried out to validate the controller operation.